Perancangan dan Implementası Sımulator Kolımator Sebagaı Medıa Pembelajaran Topık Sınar-X - Agatha Mahardika Anugrayuning Jiwatami; Sukma Meganova Effendi; Nugroho Budi Wicaksono (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
A collimator simulator which is an accessory in radiology equipment, has been made. This simulator was created as a learning medium to complete students' understanding in studying x-rays as part of electromagnetic waves. The research is divided into two stages, namely the manufacture of simulators and implementation as teaching materials. The collimator simulator is equipped with blades that are used to limit the radiation field area. In this study, collimator lamps were used to see the area of the field. The simulator is equipped with a motor to open and close the radiation window. The results of the implementation to students stated that students agreed that the collimator simulator learning media helped students to better understand the material. Keywords: learning media, collimator, radiation field area